2019
DOI: 10.1371/journal.pone.0224748
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of genital human papillomavirus among women in Southwestern, Nigeria

Abstract: BackgroundPersistent infections with high-risk genital Human papillomavirus (HPV) especially types 16 and 18, are associated with cervical cancer. However, distribution of HPV types varies greatly across geographical regions and the available vaccines target only few types. This study was designed to determine the HPV types circulating in Southwestern Nigeria, thereby providing necessary information for effective control of the virus.MethodsEndocervical swab samples were collected from a total of 295 consentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 69 publications
8
19
2
Order By: Relevance
“…However, the present study revealed no significant correlation between parity and HPV infection rate. Although, our results are consistent with results of previous studies indicating that there is no significant association between HPV infection and parity, there are still insufficient data to precisely determine the effect of parity on the risk of HPV infections. Close monitoring of HPV infection in women in China is recommended because of the replacement of the one‐child policy with a universal two‐child policy …”
Section: Discussionsupporting
confidence: 90%
“…However, the present study revealed no significant correlation between parity and HPV infection rate. Although, our results are consistent with results of previous studies indicating that there is no significant association between HPV infection and parity, there are still insufficient data to precisely determine the effect of parity on the risk of HPV infections. Close monitoring of HPV infection in women in China is recommended because of the replacement of the one‐child policy with a universal two‐child policy …”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been reported in previous research studies in American and British populations 37,38 . Studies showing an effect of race and social class on HPV prevalence are often not comparable due to differences in the included population [39][40][41] , which is generally limited to specific groups. Behavioral characteristics, such as smoking and number of partners, may explain differences in prevalence rates according to region.…”
Section: Discussionmentioning
confidence: 99%
“…For data or data subsets of the same population that were published in multiple reports [13,14], the articles were independently considered based on the different primers which were used to determine dissimilar overall HPV prevalence. While one study [13] reported the HPV genotype distribution, the other study [14] which involved the same population reported the cervical cancer screening data. One study [15] included data from Nigeria Women representing multiple states of the Federal Republic of which was data from one of the states were captured in another study [16].…”
Section: Data Itemsmentioning
confidence: 99%
“…Data were collated from studies conducted between 2004 [18] and 2019 [13,[19][20][21][22]. Except for the southeastern region of Nigeria where there were no data generated, all HPV genotyping of Nigerian participants were conducted in laboratories in North-central [15,16,20], North-east [23], North-west [15,22] and South-west [13,14,17,18,24] and South-south [25]. Two studies reported multiple infections with any specific HPV-type.…”
Section: Study Characteristicsmentioning
confidence: 99%